Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Muscicolous Lepraria species and other leprarioid lichens in the Antarctic - Botnen, Astri; Øvstedal, Dag Olav (Polar Research, 1988)
Keywords: Dronning Maud Land; botanikk; forskning; lav; planter

I fotsporene til Robert Falcon Scott - Danning, Petter (Været: populærvitenskapelig tidsskrift, 1988)
Keywords: Antarktis; ekspedisjoner; historie

Biochemical genetics and population structure of Euphausia superba - Fevolden, Svein Erik (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1988)
Keywords: Sørishavet; biokjemi; krill; plankton

Genetic population structure of Euphausia superba DANA in the Atlantic Sector of the Southern Ocean as demonstrated by different electrophoretic techniques - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1988)
Electrophoretic analyses of allele distributions at nine polymorphic gene loci were conducted in samples of Euphausia superba from the Bransfield Strait, off the South Orkney Islands, and from the south-eastern part of the Weddell Sea. The aim was to determine whether reported phenotypic differences between krill stocks from these areas could be linked to genotypic differences. Despite minor deviations of genotype distributions from Hardy-Weinberg expectations, the data gave no evidence of genetic heterogeneity over the sampled area, and the hypothesis of a single genetically homogeneous krill population could not be rejected. Genetic data for four selected loci were verified by using two different electrophoretic methods. Results from these two techniques yielded no discrepancies in interpretation of the data.
Keywords: Sør-Orknøyene; Sørishavet; Weddellhavet; genetikk; krill; marin biologi; plankton

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Navigation to nest site in the snow petrel (Pagodroma nivea) - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (The Condor, 1988)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Size variation in the snow petrel Pagodroma nivea - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (Notornis, 1988)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Proposed terminology and reporting units for sea ice algal assemblages - Horner, Rita A; Syvertsen, Erik E; Thomas, David P; Lange, Carina (Polar Biology, 1988)
Keywords: Antarktis; alger; havis; marin biologi; polarområdene; sjøis

Borekjerner fra Antarktis - hva kan de fortelle om fortidens klima? - Kanestrøm, Ingolf (Været: populærvitenskapelig tidsskrift, 1988)
Keywords: Antarktis; iskjerner; klimaforskning

Mot 90⁰ syd, en rapport - Kristensen, Monica (Polarboken, 1988)
Keywords: Antarktis; ekspedisjoner; glasiologi

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Minnesmerket på Østre Halsen over antarktispioneren C.A. Larsen - Larsen, Hans-Kjell (Polarboken, 1988)
Keywords: Sørishavet; biografi; historie; hvalfangst

Evidence for deuteric magnetization in hydrothermally altered Mesozoic basaltic rocks from East Antarctica - Løvlie, Reidar (Physics of the earth and planetary interiors, 1988)
Mesozoic basaltic lavas and dykes from Vestfjella, East Antarctica, are dominated by well-grouped, single-component palaeomagnetic directions of normal polarity. Reversed magnetizations, heavily overprinted by normal polarity components, were encountered in a few lava flows and dykes. Only thermal demagnetization was successful in separating tight distributions of reversed polarity directions, interpreted to represent a deuteric magnetization. The region has been exposed to regional hydrothermal alteration to the epidote/prehnite metamorphic facies (T ≈ 300°C). Titanomagnetite grains in high-temperature oxidation classes II–III show alteration features typical for hydrothermally altered basalts; partial to complete replacement of both ilmenite and magnetite to sphene is common in the most altered rocks, which also exhibit varying degrees of decomposition of the opaque minerals. The lavas display two major, but distinctly different, thermomagnetic curves; the ‘kink’ type, previously reported from rocks exposed to the epidote metamorphic facies, and curves dominated by a paramagnetic contribution defining a magnetite Curie point. It is concluded that the basalts have retained palaeomagnetic directions acquired during the deuteric cooling phase, implying that granulation/sphene formation and Fe depletion of decomposed titanomagnetite grains in classes II–III do not necessarily cause complete remagnetization or the acquisition of significant secondary remanent magnetizations.
Keywords: Dronning Maud Land; geofysikk; geokjemi; geologi

Census of breeding Antarctic petrels Thalassoica antarctica and physical features of the breeding colony at Svarthamaren, Dronning Maud Land, with notes on breeding snow petrels Pagodroma nivea and south polar skuas Catharacta maccormicki - Mehlum, Fridtjof; Gjessing, Yngvar; Haftorn, Svein; Bech, Claus (Polar Research, 1988)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Antarctic icebergs: production, distribution and disintegration (abstract) - Orheim, Olav (Annals of Glaciology, 1988)
A programme of systematic iceberg observations was initiated in 1981 by Norsk Polarinstitutt through the SCAR Working Group on Glaciology. Icebergs are recorded every 6 h and in five length groups: 10-50, 50-200, 200-500 and 500-1000 m, and those over 1000 m, which are described individually. Data on more than 100 000 icebergs are now on file at Norsk Polarinstitutt, and practically all ships travelling to and from Antarctica participate in the collection of data. This paper presents the first comprehensive analysis of the iceberg data. The quality of the data set is discussed, with consideration of potential errors in and limitations of the data, and various statistical evaluations. Representative distribution data are presented, and used to determine iceberg production, disintegration and mean residence times, and regional and total Antarctic calving rates. The incidence of large-scale calving in particular is evaluated, including the remarkably large break-offs in recent years. These exceed both the total annual accumulation on the Antarctic continent and the mean annual calving rate as determined from ship observations. The results show further: (1) that there are more than 200 000 icebergs south of the Antarctic Convergence, (2) that there are large regional differences in iceberg calving rates and iceberg sizes, and (3) that the calving rate from Antarctica is higher than that given in most previous estimates, which implies (4) that the mass balance of the Antarctic ice sheet is not positive as suggested by most recent estimates.
Keywords: Sørishavet; glasiologi

Numerical Analysis of Landsat Thematic Mapper Images of Antarctica: Surface Temperatures and Physical Properties - Orheim, Olav; Lucchitta, Baerbel K (Annals of Glaciology, 1988)
Keywords: Dronning Maud Land; glasiologi; innlandsis; satellittbilder; topografi

Cladonia galindezii, a new Antarctic lichen species - Øvstedal, Dag Olav (Cryptogamie, Bryologieet Lichénologie, 1988)
Keywords: Antarktis; botanikk; lav; planter

On the variation of Ochrolechia parella in the western Antarctic and Subantarctic area - Øvstedal, Dag Olav (Polarforschung, 1988)
Keywords: Antarktis; botanikk; lav; planter

Ekspedisjonen til Peter I Øy - Svendsen, Knut; Eiken, Trond (Polarboken, 1988)
Keywords: Peter I. Øy; ekspedisjoner; kartlegging; naturvitenskap